Measuring and ranking the sustainability of Mahshahr port neighborhoods from the perspective of healthy city indicators using Ida\'s technique - mehdi hemati; sadegh besharatifar; mohsen agaee (تحقیقات کاربردی علوم جغرافیایی)
The standard of health is one of the fundamental human rights throughout the world. Today, the healthy city approach is considered as one of the dominant approaches in urban and rural studies and even on a national scale. The present study was descriptive-analytical with the aim of analyzing the stability of neighborhoods in the city of Bandar Mahshahr from the perspective of healthy city indicators, in the form of three components of economic, social and environmental and 22 sub-indicators based on 2016 statistics in different neighborhoods of Bandar Assess and evaluate Mahshahr. Using T.Test test in SPSS software to measure the overall stability of the studied indicators, then the weights obtained from the critical method and Idas technique in the GIS environment compared to the ranking and leveling of neighborhoods in the integrated index in terms of  The indicators of a healthy city were taken and in the last step, through the path analysis model in pls software, the most effective factor related to sustainability in Mahshahr city neighborhoods were measured and extracted. The analysis of the findings shows that out of 35 neighborhoods studied  Only 1, 2, 6, 11 neighborhoods are in a stable and developed condition in terms of having healthy city indicators,. Keywords: sustainable, sustainable neighborhoods, healthy city, Idas technique, Mahshahr port city